PENERAPAN 5R (RINGKAS, RAPI, RESIK, RAWAT, RAJIN) TERHADAP HASIL JAHITAN BUSANA WANITA SISWA SEKOLAH MENENGAH KEJURUAN - Titis Aryanti (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2019)
The purpose of this study was to determine the effect of applying 5R (Concise, Neat, Clean, Care, Diligent) on the results of women's fashion stitches. This research is an ex-post facto type. The population amounted to 117, the sampling technique using the Issac and Michael formula at a significant level of 5% obtained a sample of 90 students. The method of data collection uses the questionnaire and documentation method. The data analysis technique is descriptive and hypothesis testing uses the Product Moment correlation test. The results of the study showed that there was a positive and significant effect of the application of 5R on the results of the stitches with a contribution of 31.1%. The 5R when learning sewing practices is mostly classified as sufficient with a relative frequency of 74.44%. Most stitches are in the good category with a relative frequency of 62.22%.